2022
DOI: 10.3390/horticulturae8060546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foaming Conditions on Foam Properties and Drying Behavior of Powder from Magenta (Peristropheroxburghiana) Leaves Extracts

Abstract: In manufacturing food powders, foam-mat drying provides a cost-effective alternative to traditional drying methods. This study aimed to select the foaming conditions which support the subsequent drying of Magenta leaves extract. In the initial stage, concentrations of egg albumin (5 to 15%) as a foaming agent, xanthan gum as foam stabilizer (0.1 to 0.5%), and whipping time (2 to 8 min) were designed. Multiple regression analysis was applied to analyze the relationship between the dependent variables (expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
4
24
1
Order By: Relevance
“…The albumin content used in this study was lower than that of the published literature. Thuy et al [ 14 ] investigated the foam-mat drying of magenta leaf extracts and found that the optimum egg albumin and whipping time values were 12.21% and 5.8 min, respectively; their foam expansion values were lower (298.12%) than in our work. Affandi et al [ 39 ] investigated the manufacturing of a Nigella sativa beverage powder and observed optimal foaming parameters of 15% egg albumen, 0.69% methylcellulose, and an 8 min whipping time.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The albumin content used in this study was lower than that of the published literature. Thuy et al [ 14 ] investigated the foam-mat drying of magenta leaf extracts and found that the optimum egg albumin and whipping time values were 12.21% and 5.8 min, respectively; their foam expansion values were lower (298.12%) than in our work. Affandi et al [ 39 ] investigated the manufacturing of a Nigella sativa beverage powder and observed optimal foaming parameters of 15% egg albumen, 0.69% methylcellulose, and an 8 min whipping time.…”
Section: Discussioncontrasting
confidence: 63%
“…In order to overcome these drawbacks, foam-mat drying, which is a technique of foaming from a liquid, has the ability to alleviate this issue. The liquid is beaten to make a stable foam before being dried on a foam pad at low temperatures [ 14 ]. Foam-mat drying is appropriate for heat-sensitive, dense, and sticky materials that cannot be dried using other methods such as spray drying; mulberry juice is an example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area of the dried product is increased, leading to the time required to dry the foamed product being reduced compared with the non-foam dried product (23). However, the foam system is not stable, resulting in difficulty in drying and removing water from the drying surface (24) and led to the dried powder product having poor color, texture, taste and nutritional value (24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Drying at 60 and 65 • C for 4 h, the moisture content of the powder was 5.82% and 5.78%, respectively, which had no significant difference between them. When drying at 70 • C for 3.5 h, the foam system has a moisture content suitable for grinding into powder; however, when drying at high temperature for a long time, the powder is easily changed, oxidized, and decomposed [33,35,36]. According to Wilkowska et al [37], blueberry powder with a moisture content of 3.9% was satisfactory in terms of quality and suitable for storage.…”
Section: Extraction Optimization Of Crocin-modeling the Effectsmentioning
confidence: 99%